Exporting activity in rural regions: does it differ from urban regions? Evidence from Poland - Nazarczuk, Jarosław M.; Umiński, Stanisław; Márquez-Ramos, Laura (Technological and Economic Development of Economy, 2024)
Limited export potential can impede growth prospects. While core regions serve as hubs of globalization, the question remains as to how rural regions can increase their exports. By identifying the factors that enhance the export competitiveness of rural regions, particularly in comparison to urban regions, we can steer them towards sustainable development and overcome constraints related to remoteness. However, there is no simple or shortcut way of increasing exports in rural regions. It still requires long-term investments, improvements in human capital, inflows of foreign-owned entities, and advantageous operations of special economic zones. Social capital has a positive impact on exports at the regional level, but its effect could not be acknowledged in the subsets of regions. What should rural regions prioritise? Investing in human capital and promoting non-agricultural economic activities that have a greater impact on rural exports than urban ones.First published online 05 March 2024